2021
DOI: 10.3389/fendo.2021.722656
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Metabolome Profiling for the Diagnosis of Catecholamine Producing Tumors

Abstract: ContextPheochromocytomas and paragangliomas (PPGL) cause catecholamine excess leading to a characteristic clinical phenotype. Intra-individual changes at metabolome level have been described after surgical PPGL removal. The value of metabolomics for the diagnosis of PPGL has not been studied yet.ObjectiveEvaluation of quantitative metabolomics as a diagnostic tool for PPGL.DesignTargeted metabolomics by liquid chromatography-tandem mass spectrometry of plasma specimens and statistical modeling using ML-based f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Two recent studies of plasma from patients with PPGL used targeted LC-MS/MS with an extended panel of over 100 metabolites. Unfortunately, low patient numbers and high inter-individual differences may have prevented the identification of suitable signatures for PPGL diagnosis, but it was demonstrated that the metabolic aberrations that occurred with PPGL were reversed after surgery (Marz et al, 2021, Erlic et al, 2019.…”
Section: Metabolome-guided Diagnostics and Future Directionsmentioning
confidence: 99%
“…Two recent studies of plasma from patients with PPGL used targeted LC-MS/MS with an extended panel of over 100 metabolites. Unfortunately, low patient numbers and high inter-individual differences may have prevented the identification of suitable signatures for PPGL diagnosis, but it was demonstrated that the metabolic aberrations that occurred with PPGL were reversed after surgery (Marz et al, 2021, Erlic et al, 2019.…”
Section: Metabolome-guided Diagnostics and Future Directionsmentioning
confidence: 99%
“…No biochemical pathway could be identified with these thirteen metabolites via principal component analysis (see Supplementary Figure S1). At 1-year follow-up patients of the RYGB-surgery group achieved a significant weight loss of −34.3% (BMI 49.1 [46][47][48][49][50][51] kg/m 2 vs. 32 [30][31][32][33] kg/m 2 , p < 0.01) as well as a significant improvement in IR measured by the Homeostatic Model Assessment for Insulin Resistance (HOMA-IR) (5.1 [4.6-6.1] vs. 1.4 [1-1.9], p < 0.01). In contrast, a non-significant weight loss of −1.2% (BMI 48.2 [45][46][47][48][49][50] vs. 47.5 [45][46][47][48][49] kg/m 2 , p = 0.07) was detected in the LS group one year after randomization.…”
Section: Participants From the Was Trialmentioning
confidence: 99%
“…The Biocrates AbsoluteIDQ p180 kit simultaneously identifies and quantifies 188 metabolites including 21 amino acids, 21 biogenic amines, 40 acylcarnitines, 15 sphingolipids, 14 lysophosphatidylcholines, 76 phosphatidylcholines and 1 hexose (>90% glucose). The assay-specific procedures have been described in detail elsewhere [49,50].…”
Section: Targeted Metabolomicsmentioning
confidence: 99%
“…Recently, plasma metabolomics by mass spectrometry (MS) proved useful for the quantification of predetermined tumor markers and for the identification of cancer-associated metabolomic profiles [ 22 24 ]. In patients affected with chromaffin PGLs a targeted metabolomic approach demonstrated changes in the concentration of specific amino acids (ornithine, sarcosine, tyrosine, creatinine, histidine, threonine) and lysophosphatidylcholine, that correlated with the results of the urine catecholamines and plasma free metanephrines tests [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%